THE ROLE OF OCULAR BLOOD FLOW IN THE PATHOGENESIS OF GLAUCOMA - Yulia Primitasari; Evelyn Komaratih (Universitas Syiah Kuala, 2019)
Abstract. Glaucoma is currently the second leading cause of blindness worldwide and the prevalence is expected to increase. Despite lowering of IOP, vascular risk factors, genetics, and other systemic conditions could progress the glaucoma damage. Ocular blood flow has emerged as an increasingly prevalent glaucoma risk factor in large population-based trials. Abnormal perfusion and the subsequent ischemia of the ONH play a major role in the glaucomatous damage. Ocular Blood flow is unstable if IOP fluctuates on a high enough or blood pressure on a low enough level to exceed temporarily the autoregulation capacity. IOP fluctuation is also related to both an increase in scotomas and an increase in diffuse visual fields damage. OBF is unstable if autoregulation itself is disturbed. In glaucoma the response of retinal and optic nerve head blood flow to flicker stimulation is reduced. Primary vascular dysregulation appears to be associated with abnormal retinal neurovascular coupling, because vasospastic subjects show a reduced response to flicker stimulation.Keywords: ocular blood flow, glaucoma